PENGARUH IMPLEMENTASI VISI DAN BUDAYA ORGANISASI DALAM PENDIDIKAN TERHADAP MUTU PENDIDIKAN - Akbar, Reza Aulia; Rukanto, Rukanto (Graduate Program Magister Manajemen Pendidikan, 2017)
The number of competition in the educational world in Indonesia requires educational institutions have value added to be selected and trusted by the community. The added value can be implemented as the quality of education in which the educational institution provides a guarantee of communitiesâ satisfaction as consumer. The quality of institutions should respond to the demand changes occur in society. In order to meet the demand and community needs the educational institutions should be built with an organizational culture that provides strength for the implementation of quality process. This research used quantitative, and the questionnaire was used as instrument. The results of this study indicate that the implementation of vision and culture of healthy organization stimulant can improve the quality of education in YWKA High School of Palembang. In other words, the implementation of vision has a significant impact on the quality of education. Evident from the results of statistical showed that the value of R Square (R2) was 0.985 (98.5%), the figure illustrates that the percentage contribution of independent variables vision and organizational culture influence 98.5% while the rest of 1, 5% influenced by other variable not examined in this research.Â Keywords: Vision, Organizational Culture, Educational Institutions, Educational Quality.